EXAMINING THE ROLE OF DIGITAL MARKETING AND PRICE DISCOUNTS IN SHAPING PURCHASE DECISIONS IN TIKTOK SOCIAL COMMERCE - Hepiana Patmarina; Rosa Wulandari (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of digital marketing and price discounts on purchase decisions for Jiniso products on TikTok Shop. It seeks to examine both the individual and synergistic effects of these marketing mix elements within Indonesia’s dominant social commerce platform. This quantitative study employs a survey approach with purposive sampling. Data were collected from 100 consumers who had purchased Jiniso products via TikTok Shop using a structured online questionnaire. Multiple linear regression analysis was conducted to test the hypothesized relationships after ensuring data validity, reliability, and meeting classical assumptions. The results indicate that both digital marketing (β = 0.248, p = 0.001) and price discounts (β = 0.581, p = 0.000) have significant positive effects on purchase decisions. Price discounts emerged as the dominant driver, with standardized coefficients more than twice that of digital marketing. Collectively, both variables explain 74.9% of the variance in purchase decisions (R² = 0.749, F = 144.792, p = 0.000), confirming their powerful synergistic effect. The findings suggest that Jiniso and similar fashion brands should maintain value-centric discount strategies while integrating them with high-quality digital content. Brands should use engaging digital marketing for top-funnel awareness and targeted discounts for bottom-funnel conversion. The optimal strategy involves creating a seamless integration between compelling content and competitive pricing on TikTok Shop. This research contributes to the literature by empirically examining the concurrent influence of digital marketing and price discounts within the specific context of TikTok social commerce in Indonesia. It provides novel insights into the relative importance and synergistic interaction of these elements in driving purchase decisions, addressing a gap in platform-specific marketing research in emerging markets.